Melanocortin-4 Receptor (MC4R) Gene as the Main Gene for Rapid Growth Selection in Beef Cattle - Peni Wahyu Prihandini; D Maharani (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2019)
Genetic improvement for economic traits such as growth is important in beef cattle selection program. This paper discusses melanocortin-4 receptor (MC4R) gene as a candidate gene for rapid growth based on its function, location and pathway, as well as its polymorphism and identified genotypes associated with economic traits, and its application as a marker-assisted selection. MC4R is a prominent gene encoding growth traits and has a critical role in mediating the effect of leptin in regulating food consumption and energy balance. Many identified MC4R gene polymorphisms are associated with growth traits. The MC4R gene, therefore, is considered as a functional candidate gene for growth traits and can be used as a marker in selection program based on molecular genetics. The use of molecular markers such as MC4R gene, therefore, can be applied in genetic improvement program for growth traits in cattle. By using MC4R gene, the efforts to build breeding system in small populations can be proposed. For instance, with an effective population size (Ne) of about 40 heads, the first generation (G1) will be obtained with a composition of GG 61.1%, CG 33.3% and CC 5.6% and male and female ratio of 178:11 and generates ideal Ne of 41 heads. In the third generation, therefore, GG composition will be 100%. The results of molecular analysis can be further used as a guideline in the development and genetic improvement strategies of beef cattle.